THE IMPACT OF TECHNOLOGY ON CHILDREN’S VOCABULARY CAPACITY - Nargis; Bunga Malika Putri; Erningsih Putri S; Fauzan Rofiqi; Khilda Umi Rahmah (Media Inovasi Pendidikan dan Publikasi, 2024)
This study examines the influence of technology on children's vocabulary development, focusing on a case study of a three-year-old boy named Rizky. Despite Rizky's enthusiasm for learning through YouTube videos, his vocabulary was initially limited to words from the videos. His mother, Ibu Maya, creatively intervened by incorporating interactive play, real-world interactions, and reading sessions to expand his vocabulary. This approach demonstrates the necessity of balancing digital media with traditional learning methods and highlights the role of parental involvement. Theoretical frameworks such as Dual Coding Theory and Social Learning Theory provide insights into the effectiveness of this combined approach.